Occupational exposures and mammographic density in Spanish women (2018)
Abstract Objectives The association between occupational exposures and mammographic density (MD), a marker of breast cancer risk, has not been previously explored. Our objective was to investigate the influence of occupational exposure to chemical, physical and microbiological agents on MD in adult women. Methods This is a population-based cross-sectional study based on 1476 female workers aged 45–65 years from seven Spanish breast cancer screening programmes. Occupational history was surveyed by trained staff. Exposure to occupational agents was assessed using the Spanish job-exposure matrix MatEmESp. Percentage of MD was measured by two radiologists using a semiautomatic computer tool. The association was estimated using mixed log-linear regression models adjusting for age, education, body mass index, menopausal status, parity, smoking, alcohol intake, type of mammography, family history of breast cancer and hormonal therapy use, and including screening centre and professional reader as random effects terms. Results Although no association was found with most of the agents, women occupationally exposed to perchloroethylene (e?=1.51; 95% CI 1.04?to 2.19), ionising radiation (e?=1.23; 95% CI 0.99?to 1.52) and mould spores (e?=1.44; 95% CI 1.01?to 2.04) tended to have higher MD. The percentage of density increased 12% for every 5?years exposure to perchloroethylene or mould spores, 11% for every 5?years exposure to aliphatic/alicyclic hydrocarbon solvents and 3% for each 5?years exposure to ionising radiation. Conclusions Exposure to perchloroethylene, ionising radiation, mould spores or aliphatic/alicyclic hydrocarbon solvents in occupational settings could be associated with higher MD. Further studies are needed to clarify the accuracy and the reasons for these findings.